Engineered Small Extracellular Vesicles as a FGL1/PD‐L1 Dual‐Targeting Delivery System for Alleviating Immune Rejection (Adv. Sci. 3/2022). Issue 3 (25th January 2022) - Tsai, Hsiang‐i; Wu, Yingyi; Liu, Xiaoyan; Xu, Zhanxue; Liu, Longshan; Wang, Changxi; Zhang, Huanxi; Huang, Yisheng; Wang, Linglu; Zhang, Weixian; Su, Dandan; Khan, Fahim Ullah; et al.
Abstract : Small Extracellular Vesicles The simultaneous high expression of LAG‐3 and PD‐1 on T cells in cardiac transplantation mouse models and clinical renal transplantation patients provides the possibility to establish immune tolerance by giving their ligand molecules. In article number 2102634 by Bo Jia, Fang Cheng, Hongbo Chen, and co‐workers, small extracellular vesicles derived from bioengineered PD‐L1/FGL1‐expressed mesenchymal stem cells encapsulated with low‐dose FK506 exerted a powerful synergistic inhibitory effect on T cell activation and, therefore, prolonged grafts survival.